ENHANCING STUDENT ENGLISH WRITING SKILLS THROUGH PROJECT-BASED LEARNING - Yuliana, Fitri; Sahayu, Wening (English Review: Journal of English Education, 2024)
Writing becomes one of the most difficult skills to be experted by the students, especially in high school level. Therefore, Project Based-Learning is offered to solve the difficulties that were faced by the students in writing. Some experts believed that Project Based-Learning could help students to develop their writing skills through the projects given by the teacher. This research reports on the implementation of Project Based-Learning in teaching writing, especially news text. The objectives of this research were to describe the improvement of the student’s writing skill through Project Based-Learning and to describe the students’ attitudes in learning English writing skill through Project Based-Learning. This research used qualitative method and classroom action research as a research design. The participants of the research were 21 students of tenth grade of MA Diponegoro Yogyakarta. The collected data were obtained through observation, writing test, and interview. The data were analysed based on triangulation. As result, it was found that the implementation of Project Based-Learning in teaching writing worked well. It could be seen from the students’ responses and development during the implementation of this method.